Derrame pleural benigno por exposição a asbestos. - J R Vieira; E Alfarroba; J Viegas; M Freitas e Costa (Acta Médica Portuguesa, 1992)
The Authors present the first case described among us of benign pleural effusion of an asbestotic origin. They stress the importance of thoracoscopy (pleuroscopy) in the diagnosis of this situation. Attention is drawn to the fact that asbestotic lesions and asbestotic bodies have been found in the lung and, in particular, in the parietal pleura as well. They emphasize the fact that exposure to asbestos was not realized by the patient, which made the clarification of the situation more difficult. It was a CT scan that showed the signs suggestive of exposure to asbestos which raised the diagnostic suspicion. They conclude that every patient with a pleural effusion must be thoroughly questioned about exposure to asbestos. Even if the exposure is accepted, they consider that one should proceed to a pleuro-pulmonar biopsy by thoracoscopy. This biopsy allows demonstration of the characteristic histopathological lesions and rule out other etiologies, namely malignancy and tuberculosis. They suggest that these patients must be highly motivated to stop any smoking and kept under periodic surveillance.